Effect of skill acquisition on enterprise creation among Malaysian youths - Isidore Ekpe; Razli Che Razak (Czestochowa University of Technology, 2016)
This study aims at investigating whether moderating factors such as self-motivation and social influence could hinder skill acquisition from resulting to enterprise creation among Malaysian university graduates. A survey, and proportionate stratified random sampling method, was adopted to collect data from a sample of 240 youths in Malaysia peninsula. Data were analyzed using descriptive statistics and hierarchical regression methods. One of the results reveals that self-motivation moderated between skill acquisition and enterprise creation among the youths. The study recommends that more counseling from parents, universities, governments and other stakeholders be given to youths to engender greater interest in enterprise creation.